The economic analysis of consumer attitudes towards food produced using prohibited production methods: Do consumers really care? - Kelvin G. Balcombe; Dylan Bradley; Iain M. Fraser (University of Kent, School of Economics, 2020)
We report the findings from a hypothetical discrete choice experiment (DCE) examining UK consumer attitudes for food produced using agricultural production methods currently prohibited in the UK i.e., hormone implants in beef; Ractopamine in pig feed; chlorine washed chicken; and Atrazine pesticide. Our results reveal that on average the public have very negative values for these forms of agricultural production methods. We also find that respondents highly value food products that observe EU food safety standards. Our willingness to pay estimates show that the positive values for food safety are frequently greater than negative values placed on the food production methods examined. Similarly, UK country of origin was highly valued but organic production was not valued as highly. These results clearly indicate that the only attribute that is negatively valued across all DCE are the production methods that are currently not allowed within the EU or UK.
Keywords: 330; Discrete Choice Experiment; Willingness to Pay